Kesiapan Kawasan Transit Solo Balapan dalam Pengembangan Transit Oriented Development - Rosari, Bertania Kartikaning Tiyas; Permana, Chrisna Trie Hadi; Rahayu, Murtanti Janti (REKSABUMI, 2024)
The city of Surakarta is rapidly developing towards metropolitan, driving the formation of travel patterns to and from Surakarta where the station points become one of the main points. The role of Solo Balapan Station as the core transportation hub connecting Surakarta's internal and external areas has necessitated the design of an integrated transportation system with urban hubs or centers. Transit Oriented Development becomes an alternative concept designed to organize and develop activity centers in an area with land use variations integrated with urban transportation systems. Although some efforts have been shown as a seriousness of the government, it is not yet known for certain whether the characteristics of the supporting areas in the research area are ready to support the development of areas based on the TOD concept. This research is conducted in order to assess the extent to which the characteristics of supporting areas within an 800-meter radius around Solo Balapan Station support the development of the TOD concept. This research uses quantitative descriptive analysis through scoring analysis. The results show that the supporting area around Solo Balapan is not ready to support the development of the area with the Transit Oriented Development concept.